2019
DOI: 10.3329/baj.v21i2.44494
|View full text |Cite
|
Sign up to set email alerts
|

Response of Mustard to Soil Test Based Fertilizer Management

Abstract: A field experiment was carried out at Sonapur of Muradnagar upazilla in Cumilla district under the Debidwar MLT (Multi-Location Testing) site during the rabi season of 2013-15. The experiment was conducted in the Old Meghna Estuarine Floodplain (AEZ-19) soil. The experiment was laid out in randomized complete block design (RCBD) with 3 replications.The treatments were: T1= Soil Test Based (STB) Fertilizer dose (FRG 2012), T2= T1+ 15% STB, T3= T1+ 30% STB, T4= 80% STB from inorganic fertilizer + 20% STB from CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Mamun et al [10] reported that using Soil Test Basis (STB) fertilizer recommendation method give more effective tillers hill -1 . Akhter [11] carried out a series of experiment about the effect of different fertilizer recommendation methods on rice and confirmed that fertilizer recommended through BAU soil testing kit gave highest panicle length, filled grains panicle -1 , 1000-grain weight, and yield. In rice grain, the highest N content (1.288%) was observed with BAU Soil Testing Kit (T4), while all treatments showed significantly higher nitrogen content compared to the control (Table 6).…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Mamun et al [10] reported that using Soil Test Basis (STB) fertilizer recommendation method give more effective tillers hill -1 . Akhter [11] carried out a series of experiment about the effect of different fertilizer recommendation methods on rice and confirmed that fertilizer recommended through BAU soil testing kit gave highest panicle length, filled grains panicle -1 , 1000-grain weight, and yield. In rice grain, the highest N content (1.288%) was observed with BAU Soil Testing Kit (T4), while all treatments showed significantly higher nitrogen content compared to the control (Table 6).…”
Section: Resultsmentioning
confidence: 79%
“…The highest total nitrogen uptake by rice has also found in treatment T4 (108.84 kg ha -1 ). Akhter [11] reported that the plots treated by fertilizer recommended through BAU soil testing kit show higher content and N uptake in rice. The higher N uptake might be attributed to higher N application in BAU soil testing kit based fertlizer recommendation method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation